The Importance of Religious Festivals to Promote Cultural Heritage in Turkey and India - Munshi, Alaknanda (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2022)
Celebrating religious festivals is a public expression of beliefs that strengthens the believer's relationship with God. Different religions, such as Christianity, Judaism, and Islam, regard celebration as one of the ceremonies that believers are mandated or urged to practice. Religious festivals can boost spirituality among believers and boost the local economy by generating revenue, supporting existing businesses, and encouraging new enterprises to start up. Religious festivals can boost their image and focus as a cultural destination by engaging in promotional activities. This study aims to examine religious festivals in Turkey and India to promote cultural heritage. This research employs a qualitative method by reviewing scientific articles, books, and journals. The result of this study revealed that festivals are an essential form of cultural tourism in which cultural activities are leveraged to generate more visitors. Religious festivals can strengthen their cultural heritage and become more focused as a cultural destination by engaging in promotional activities. While the organizer partly determines a festival's success, if a festival is not effectively organized, the destination will lose revenue and its image. These play a vital role in the cultural development process. In this light, this research will analyze the religious festivals in Turkey and India through cultural heritage and their extent and relationship to tourism development.